Investigating the impact of muckrakers on American society issues in the Progressive Era (1896-1916):Ida Tarbell as a Model - Houri, Ben Amor, Ibtihal Ibtissam (University of El-oued, 2022)
This study explores the effects of Ida Tarbell's works as the muckraker on American society during the Progressive Era, which witnessed many changes because of Progressives' thoughts. This dissertation aims to explain and examine the impact of muckrakers, either on the political side of the economic one, and analyze the muckraking book of Ida Tarbell, the history of the Standards Oil Company that reveals the implied corruption that was rampant excessively during that period. A descriptive and analytical method is adopted to analyzing investigative journalism's important role in showing the generated public outrage quickly catalyzed the passage of new legislation and influenced imitators overseas. The Muckrakers' work is still remembered as a high point of U.S. journalism. تهدف الدراسة الحالية لدراسة تحليل تأثير عمل إيدا تاربيل على المجتمع الأمريكي خلال العصر التقدمي ، الذي شهد العديد من التغييرات بسبب الأفكار التقدمية المنتشرة في تلك الفترة. تهدف هذه الأطروحة إلى شرح وفحص تأثير الصحافة الاستقصائية على كل من الجانب السياسي و الاقتصادي وتحليل التحقيق الصحفي في كتاب إيدا تاربيل ، تاريخ شركة ستاندرد أويل الذي يكشف عن الفساد الداخلي الذي انتشر بشكل كبير خلال العصر التقدمي. تم استخدام نهج وصفي وتحليلي لتحليل الدور المهم للتحقيقات الصحفية التي ظهرت في وقت قصير حيث أثارت مقالاتهم غضبًا عامًا ، وحفز على إصدار تعديلات تشريعية جديدة ، وأثر الكثير في الخارج. لا يزال يُذكر عمل الصحافة الاستقصائية على أنه نقطة عالية في الصحافة الأمريكية
Keywords: Ida Tarbell, Muckraker, Progressive era, The History of the Standards Oil Company; ايدا تاربيل، العصر التقدمي الصحافة الاستقصائية.